2012
DOI: 10.1128/aac.05637-11
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Functional Roles of Cationic Side Chains of the Major Antimicrobial Region of Human Cathelicidin LL-37

Abstract: Human cathelicidin LL-37 is a critical cationic antimicrobial peptide for host defense against infection, immune modulation, and wound healing. This article elucidates the functional roles of the cationic side chains of the major antimicrobial region of LL-37, corresponding to residues 17 to 32 (designated GF-17). Antimicrobial assays, killing kinetics studies, and vesicle leakage experiments all indicate that a conversion of lysines to arginines affected the ability of the peptide to kill the Gram-positive St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
151
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(159 citation statements)
references
References 68 publications
7
151
0
1
Order By: Relevance
“…It is noteworthy that studies on human cathelicidin analogs reveal that removal of hydrophobic amino acids from the N-terminal end of native LL-37 could decrease its cytotoxicity without compromising the peptide's antimicrobial efficacy toward both Gram-positive and Gram-negative bacteria (78). Wang et al (80) recently mapped and unmasked the potential roles of cationic residues of human cathelicidin LL-37 against different bacterial strains. The cationic side chains of the major antimicrobial region of human cathelicidin LL-37 were fragmented, and their functional roles were studied in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that studies on human cathelicidin analogs reveal that removal of hydrophobic amino acids from the N-terminal end of native LL-37 could decrease its cytotoxicity without compromising the peptide's antimicrobial efficacy toward both Gram-positive and Gram-negative bacteria (78). Wang et al (80) recently mapped and unmasked the potential roles of cationic residues of human cathelicidin LL-37 against different bacterial strains. The cationic side chains of the major antimicrobial region of human cathelicidin LL-37 were fragmented, and their functional roles were studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…It also indicated that the conversion of amino acids from lysines (K) to arginines (R) increased the ability of the peptide to kill S. aureus. Therefore, the use of the GF-17 fragment of LL-37 may lead to lower dosages and therefore reduced toxicity (80).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of Streptococcus of group A to perceive and respond to LL-37 may partially explain the susceptibility of humans as a biological species not only to Streptococcus of group A, but also to streptococcal infection in general [31]. Based on the data obtained, it was suggested that in the conditions of LL-37 deficiency an inversion of its action is observed, that is, instead of the expected bactericidal effect, the virulence of the microorganism increases [35].…”
Section: Resultsmentioning
confidence: 93%
“…A particular binding site in CRAMP may directly bind to 2-O-sulfated uronic acids in syndecan-1 HS or bind to a conformation of syndecan-1 HS that is dictated by 2-O-sulfated motifs. In fact, spacing of cationic amino acids is important for the anti-bacterial activity of LL-37 (61), suggesting that similar spacing of cationic residues in CRAMP may allow this peptide to avidly bind to 2-O-sulfate motifs in syndecan-1 HS.…”
Section: Discussionmentioning
confidence: 99%